Health care activism, community health, and patient-centered research - Concannon, Thomas (Henry Stewart Talks, 2023)
Health care activism, Patient-centered research, ACT UP (AIDS Coalition to Unleash Power), TAG (Treatment Action Group), HIV/AIDS treatment activism, Community-based research, Translational research and associated roadblocks, Broadly engaged team science, Science and society, Meaningful engagement